1999
DOI: 10.1038/sj.bjc.6690158
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis correlates with high vascular density and focal macrophage infiltration in invasive carcinoma of the breast

Abstract: Summary Necrosis is a common feature of invasive carcinoma of the breast and is caused by chronic ischaemia leading to infarction. Although necrosis was previously assumed to be due to a generally poor blood supply in the tumour, in this study we show that it is present in tumours with focal areas of high vascular density situated away from the actual sites of necrosis. This may account, in part, for the previous observation that necrosis is linked to poor prognosis in this disease. Highly angiogenic tumours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
311
2
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 445 publications
(358 citation statements)
references
References 16 publications
19
311
2
9
Order By: Relevance
“…Thus they have the capacity to affect tumour vascularization, growth rate, stroma formation, and apoptotic cell death (Mantovani et al, 1992). Leek et al (1997) have shown that higher numbers of macrophages are found in angiogenic breast tumours and that they are concentrated in avascular, hypoxic regions of the tumour, consistent with many other reports indicating high macrophage numbers in avascular necrotic sites . Hypoxia is known to stimulate the angiogenic activity of macrophages, and macrophage-derived VEGF is upregulated under low oxygen tensions (Harmey et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Thus they have the capacity to affect tumour vascularization, growth rate, stroma formation, and apoptotic cell death (Mantovani et al, 1992). Leek et al (1997) have shown that higher numbers of macrophages are found in angiogenic breast tumours and that they are concentrated in avascular, hypoxic regions of the tumour, consistent with many other reports indicating high macrophage numbers in avascular necrotic sites . Hypoxia is known to stimulate the angiogenic activity of macrophages, and macrophage-derived VEGF is upregulated under low oxygen tensions (Harmey et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with these theories, breast cancer patients with low macrophage indices have a lower risk of recurrence and increased overall survival rates (Leek et al, 1997), furthermore, experimental studies have shown a trend between high macrophage numbers and radioresistance (Milas et al, 1987). These studies suggest that radiobiologically hypoxic tumours are targets for angiogenic activity, presumably to improve nutrient supply and drainage, and unsurprisingly have poor response rates to therapy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations